Metadiscourse in Three Minute Thesis Presentations: An Interdisciplinary Perspective - Qiang Zhou; Xiaohui Yu; Xurui Zhang; Yashuang Liu (SAGE Open)
Three Minute Thesis (3MT) competition, as a flourishing academic genre, contributes to assisting scholars to popularize scientific knowledge to a heterogenous audience. Regarding metadiscourse of 3MT genre, much attention has been paid to the interactional features, while its interactive features have been underexplored. This study examined 3MT presentations from two planes of metadiscourse, adopting Hyland’s interactive metadiscourse framework and Qiu and Jiang’s modified model of interactional metadiscourse. To investigate the disciplinary similarities and differences between hard sciences and soft sciences, and explore the underlying reasons, this study built a 3MT corpus of 120 presentations with quantitative and qualitative approaches. Results indicate that metadiscourse devices are more abundant in hard sciences than in soft sciences (LL = 24.21, p  < .0001). Specifically, presenters of hard sciences tend to use more code glosses (LL = 30.97, p  < .0001), endophoric markers (LL = 7.4, p  < .01) and engagement markers (LL = 21.83, p  < .0001), but less evidentials (LL = 16.25, p  < .0001) than those of soft sciences. As for the other subcategories, no significant difference has been found. Our interdisciplinary findings have significant implications for providing rhetorical strategies to presenters of 3MT competition and for EAP teachers preparing students to orally present their research in other academic spoken genres.